Laser Interferometer Diagnostics of CNC Machine Tools - Jerzy Jozwik; Ivan Kuric; Leszek Semotiuk (Communications, 2014)
This paper presents diagnostics of selected CNC machine tools performed with XL80 laser interferometer with XC80 environmental compensation unit, temperature sensors and XR20-W rotary axis calibrator, working together with XL80 laser. Furthermore, the paper includes the methodology and results of conducted linear and angular error measurements, which supplied data for further analysis. The conclusion section presents results of conducted experiment. Measurement results were presented in figures, charts and tables.